Experimental study of carbon fiber reinforced alkali-activated slag composites with micro-encapsulated PCM for energy storage. (10th February 2018) - Cui, Hongzhi; Feng, Tangjie; Yang, Haibin; Bao, Xiaohua; Tang, Waiching; Fu, Jiyang
Highlights: Alkali-activated slag composites with micro-encapsulated PCM and CF were prepared for energy storage. Using CF can improve mechanical properties of both OPC-MPCM and AAS-MPCM dramatically. Mechanism of CF reinforcement in the composites was studied by microstructure analysis. CF reinforced AAS-PCM obtained maximum different temperature value with 6.8 °C. The CF reinforced AAS-PCMs are potential candidate for thermal energy storage in buildings. Abstract: The use of cement composite with phase change materials (PCM) for thermal energy storage in building is one of the effective means because PCM can be integrated into building envelopes to reduce thermal stress and improve thermal comfort. However, the manufacturing of cement requires much energy and the process involves the emission of carbon dioxide and other undesirable gases to the environment. In this study, an alkali-activated slag (AAS) was used as an alternative to ordinary Portland cement (OPC) and incorporated with various proportions of graphite-modified microencapsulated PCM (MPCM) and carbon fibers (CF) for improving functional and mechanical properties. Tests on the mechanical properties, microstructure, thermal conductivity and thermal storage capacity of the AAS-MPCM composites were carried and compared with those properties the OPC-MPCM composites. Test results show that compressive strength of the AAS-MPCM composites were higher about 30% than the OPC-MPCM composite, but all the compressive strengths generally decreased with increasing MPCM content. CF can increase mechanical properties of both OPC-MPCM and AAS-MPCM dramatically. Compared with OPC-PCM, AAS-PCM has presented well thermal storage capacity. AAS with 20 wt% MPCM and 1 wt% CF obtained maximum different temperature value with 6.8 °C and it delay 2 min compared with the control samples. Based on the results, AAS-MPCM composites can be used as a promising alternative to cement-based MPCM composites in building components to effectively increase the thermal energy storage performance of building and reduce the energy consumption for cooling and heating.